Coolies, Port au Spain, Trinidad - West, A.J. (My University, 2010)
East Indians riding donkey drawn carts in Port of Spain. Postcard numbered 3567.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; East Indians--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Ethnic costume--India; Dwellings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain